Knowledge Relationship With Level Anxiety In Patients Who Will Endoscopic Performance In General Hospital Dr. Zainoel Abidin Government Aceh 2022 - Nurromsyah Nasution; Zakiyah (Institute of Computer Science (IOCS), 2022)
Endoscopy is a tool for visual examination of internal organs, especially the gastrointestinal tract at a target by using tools that are clearly visible on the monitor and abnormalities in the organ being examined. Endoscopy anxiety caused by the procedure such as fear, pain and discomfort, inadequate information, and ignorance during the procedure. This study aims to determine the relationship between knowledge and the level of anxiety in patients undergoing endoscopy. type of Correlative Descriptive research with a Cross Sectional approach. The research sample is 60 respondents with Accidental technique. Data analysis using the chi square test with a significance level of α = 0.05 (95%). The results of the study obtained knowledge about the level of anxiety in patients undergoing endoscopy (p = 0.012 < α 0.05). The results of this study indicate that knowledge can affect the anxiety level of respondents who will perform endoscopy.